Meta-Analysis the Effects of Rotavirus Vaccine, Exclusive Breastfeeding, and Maternal Education on Diarrhea in Children Under Five - Genn Andrean Pratama; Setyo Sri Rahardjo; Bhisma Murti (Journal of Epidemiology and Public Health, 2023)
Background: Diarrhea is an infectious disease that can cause death in children under five years. Diarrheal disease is a disease with the highest mortality and morbidity after pneumonia. The purpose of this study was to analyze and estimate the effect of rotavirus vaccine, exclusive breastfeeding, and mother's education level on the incidence of diarrhea in toddlers, with a meta-analysis based on previously conducted primary studies. Subjects and Method: This article was prepared using a systematic review and meta-analytic study. This research was conducted using the PICO model. Meta-analytic studies were conducted by searching for articles from databases in electronic form using PubMed, Google Scholar, Sciencedirect, and Springer Link. Article searches were conducted from 1-28 February 2023. The keywords used were “Vacinnation” OR “Exclusive breastfeeding” OR “Educational Mother” OR “Infection” OR “Diarrhea Childhood”. The inclusion criteria for this study were complete articles using cross-sectional research, published years from 2013-2022. Analysis of the articles used RevMan 5.3 software. Results: A total of 24 cross-sectional studies from Africa and Asia were selected for systematic review and meta-analysis. The results of the meta-analysis showed that not given rotavirus vaccine had a 3.60 times the risk of experiencing diarrhea compared to those given rotavirus vaccine (aOR= 3.60; 95% CI= 2.31 to 5.64; p<0.001), not given exclusive breastfeeding had a risk of experiencing diarrhea 3.28 times compared with those who were given exclusive breastfeeding (aOR= 3.28; 95% CI= 2.24 to 4.80; p<0.001), and children who had mothers with low education levels had a 2.08 times higher risk of experiencing diarrhea compared to children who had mothers with low education levels which is higher (aOR= 2.08; 95% CI= 1.71 to 2.54; p<0.001). Conclusion: Not being given the rotavirus vaccine, not being given exclusive breastfeeding, and the mother's low education level are at risk of increasing the incidence of diarrhea in toddlers. Keywords: rotavirus vaccine, exclusive breastfeeding, mother's level of education, child diarrhea Correspondence: Genn Andrean Pratama. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: andreanpratama0077@gmail.com. Mobile: +6282278467441.